2010
DOI: 10.1021/pr100265g
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Ionization Approach for RRLC−MS/MS-based Metabonomics: Finding Potential Biomarkers for Lung Cancer

Abstract: An integrated ionization approach of electrospray ionization (ESI), atmospheric pressure chemical ionization (APCI), and atmospheric pressure photoionization (APPI) combining with rapid resolution liquid chromatography mass spectrometry (RRLC-MS) has been developed for performing global metabonomic analysis on complex biological samples. This approach was designed to overcome the low ionization efficiencies of endogenous metabolites due to diverse physicochemical properties as well as ion suppression, and obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 36 publications
3
68
0
1
Order By: Relevance
“…Taurine, hippuric acid, and carnitine were included in HMDB database as lung cancer-related biomarkers and were also reported by Yang et al [26]. Tyrosine was reported as potential biomarker of lung cancer by An et al [27] and its phosphorylated derivative was also found in our work. Uric acid concentration was found upregulated in urine samples from cancer group.…”
Section: Discovery and Identification Of Differential Metabolitessupporting
confidence: 75%
“…Taurine, hippuric acid, and carnitine were included in HMDB database as lung cancer-related biomarkers and were also reported by Yang et al [26]. Tyrosine was reported as potential biomarker of lung cancer by An et al [27] and its phosphorylated derivative was also found in our work. Uric acid concentration was found upregulated in urine samples from cancer group.…”
Section: Discovery and Identification Of Differential Metabolitessupporting
confidence: 75%
“…Eleven potential biomarkers including amino acids, nucleosides and indole were identified. The study revealed elevated amino acid and nucleoside metabolism as well as protein degradation in patients with lung cancer [55]. Previous studies indicated increased urinary aromatic amino acids that might be caused by derangement of protein metabolism in cancer patients [56].…”
Section: Lung Cancermentioning
confidence: 79%
“…Review MS-based metabolomic platforms are increasingly applied to the screening of tumor markers and have been used in recent years for colorectal cancer [39][40][41][42][43][44][45][46], lung cancer [47][48][49][50][51][52][53], papillary thyroid carcinoma [54], oral cancer [55,56] and pancreatic cancer [57]. Here, due to space limitations, the authors review the development of metabolomics in the discovery of tumor markers only for specific malignancies with high incidence, including primary liver cancer, gynecologic cancer and genitourinary cancer.…”
Section: Phenotype Classification and Early Detection Of Tumor Patientsmentioning
confidence: 99%